Enhancing oil-water flow simulation in shale reservoirs with fractal theory and meshless method - Liu, Wenbo; Zhang, Guangming (Frontiers in Environmental Science, 2023)
Introduction: Simulating oil and water flow in shale reservoirs is challenging due to heterogeneity caused by fractures. Conventional grid-based methods often have convergence issues. We propose a new approach using fractal theory and meshless methods to accurately model flow. Methods: A mathematical model describing oil-water flow in fractured horizontal shale wells was developed. The meshless weighted least squares (MWLS) method was used to numerically solve the model. Modeling points were placed flexibly, informed by fractal theory. Results: The MWLS solution aligned well with reference solutions but had enhanced flexibility. Comprehensive analysis showed the effects of modeling parameters like fracture properties on production. Discussion: The proposed methodology enabled accurate prediction of shale oil production. Convergence was improved compared to grid-based methods. The flexible modeling approach can be tailored to specific reservoir conditions. Further work could expand the model complexity and types of reservoirs.